Chirps Amidst Coronavirus Disease-2019 (COVID-19) Transmission and Prevention in Ethiopia in 2020 - Sahilu, Assegid (International Journal of Coronaviruses, 2021)
Background Ethiopia confirmed its 1st case of COVID-19 on Friday 13th February 2020. The burden increased dramatically by August/2020. The conditions that led to this rise were not reviewed. Objective To exploreCOVID-19 related phenomena in Ethiopia during 2019-2020. Materials and Methods Review of journals, books, and letters to editors, e-sources, news, personal experiences, observations, and communications. Results The zoonotic source of SARS- CoV-2 (Severe Acute Respiratory Distress Syndrome- Coronavirus-2) is not confirmed. The precedent events; and exact mechanism of COVID-19 is not clear. Dynamic models were required on the time line of dynamics of COVID-19; dynamics of infectiousness of COVID-19, and mechanism of transmission of COVID-19. Incubatory carriers might have been missed. Screening based on temperature had been problematic. The time spent in the development of diagnostic test for COVID-19 might have contributed to the early spread. Uninterrupted flights to China during the epidemic by Ethiopian Airlines as well as uninterrupted domestic flights; IDP (Internally Displaced People); and others put Ethiopia (and other countries) at great risk. Demographic adjustment may not be applicable for Ethiopia due to lack of census which had to be conducted every 10 year, was conducted only in 2007. This adds to the problem of error projection. The impact of HIV (Human Immuno-Deficiency Virus Disease) and war in Ethiopia before 2000 might have had affected people who would be now old age and who would be at the most risk of death. This made the impact of COVID-19 to appear low as revealed by the lower number of COVID-related deaths in Ethiopia. There were also hesitations inconsistencies in case definitions; implementations of quarantine; and burial regulations. Conclusion Even though uninhibited foreign flight to China as well as domestic flights; inconsistencies in the implementation of regulations pertaining to COVID-19 have contributed to COVID- 19 emergence in Ethiopia, the absence of census; the demographic impact of HIV and war before 2000 might have made the impact of COVID-19 to appear low as revealed by the lower number of COVID-related deaths in Ethiopia. Recommendation Accurate and current evaluation of the impact of COVID-19 in Ethiopia may require the absence of census; demographic consequences of HIV; and war before 2000 into consideration.
Keywords: COVID-19